2021
DOI: 10.1111/cura.12456
|View full text |Cite
|
Sign up to set email alerts
|

LEARN: Essential Elements of Museum Education Programs for Young Children

Abstract: Museums provide rich multimodal learning opportunities and long‐lasting memories for children and teachers who participate in museum excursions and outreach programs. Museum programs for preschool children embed hands‐on opportunities to engage children with new and diverse artefacts. Interactions in museum settings provide opportunities for adults and children to collaborate in learning. Our aim in this project was to explore the elements of museum programs that prove essential in engaging young children in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
1
3
0
1
Order By: Relevance
“…Similar to our results, Young et al. (2021) found that structural and interactional elements of programs work together to support children's learning at hands‐on programs. They concluded that conversation prompts are “crucial” to “creating substantive learning experiences” at well‐designed programs (p. 220).…”
Section: Discussionsupporting
confidence: 91%
“…Similar to our results, Young et al. (2021) found that structural and interactional elements of programs work together to support children's learning at hands‐on programs. They concluded that conversation prompts are “crucial” to “creating substantive learning experiences” at well‐designed programs (p. 220).…”
Section: Discussionsupporting
confidence: 91%
“…A questionnaire survey was distributed to parents of children nationwide through the Internet to collect user data further. The purpose is to get in touch with parents of children more directly, to understand the current development status of children's various abilities, as well as parents' awareness of children's right and left brain exercises and expectations of whole-brain enlightenment toys, to provide a reference basis for further case studies [ 16 ]. The questionnaire survey was distributed to collect a broader range of data nationwide through online channels to obtain more accurate and general theoretical data.…”
Section: Methodsmentioning
confidence: 99%
“…This also aimed to understand parents' perceptions of their children's capabilities and their expectations regarding art creation products. The collected data serves as a foundational reference for further case studies in this area [11]. The purpose of this survey is to utilize the gathered information and data to ascertain the psychological, behavioral, and needs aspects of children.…”
Section: Questionnaire Designmentioning
confidence: 99%